Intervensi yang Mendukung Kualitas Hidup Penyintas Tumor Otak - Renie Kumalasari; Dewi Gayatri; Yati Afiyanti (Journal of Telenursing (JOTING), 2023)
Based on previous studies ' results, this study aims to examine interventions that impact brain tumor survivors' quality of life. The method used is a literature study. Article search through Science Direct, Pubmed, and Google Scholar databases. The search keywords are brain tumor, QOL, RCT, and Intervention. The Boolean logic used is "AND" and "OR". The search also activates special filters such as article type: research article, access type: open access & open archive, and text availability, free full text. The results showed that the five themes that passed the selection were reviewed. Based on the articles reviewed, this study found that various interventions positively impacted the quality of life of brain tumor survivors. The interventions include yoga, health promotion based on Traditional Chinese Medicine (TCM) and peer support (the Ohana project), high-quality nursing, pilates-based group therapy, and ski training. The conclusions in this study illustrate the positive benefits of various interventions given to the quality of life of brain tumor survivors. These interventions include yoga, health promotion based on Traditional Chinese Medicine (TCM), peer support (the Ohana project), high-quality nursing, group therapy-based pilates, and ski training. Keywords: Intervention; Quality of Life; Brain tumor